Phonetic Features of the Manavgat (Antalya) Subdialect-II: Vowels - Celal Görgeç (Türkiyat Mecmuası)
This study introduces the phonetic features of the subdialects spoken in Manavgat, one of the biggest districts of Antalya. The study comparatively examines the vowels used in the Manavgat subdialects and their relationships to historical and contemporary Turkic written languages. The structure and features of Turkic languages are not an issue that can be solved by examining literary languages alone; subdialects can also provide powerful data in order to conclude unresolved points. The Manavgat subdialects have an important place among other Turkish subdialects with their unique phonetic features. Although Oghuz languages have a subdialect, the Manavgat subdialects have primarily preserved their archaic phonetic features. Vowel sounds shouldbe handled in depth to reveal the characteristic features of the Manavgat subdialects, which contain many phonetic, morphological, and lexical language features that are not found in standard Turkish. For this reason, this study aims to explain the features of the vowels used in the local dialects and the phonological changes that occur within the vowels. During the examinations, primary and secondary vowel lengths are seen to be encountered in the region. Phonetic features are also found that can be considered Kipchak elements in the local dialects or that can be evaluated in the context of language relations. This study will contribute to Turkic language research and dialect atlas studies, which suffer from major deficiencies in the field of dialectology.